2011
DOI: 10.1371/journal.pone.0016285
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Enhancing Effect of Prostatic Acid Phosphatase Peptides Is Reduced in Human Seminal Plasma

Abstract: We recently reported that HIV-1 infection can be inhibited by innate antimicrobial components of human seminal plasma (SP). Conversely, naturally occurring peptidic fragments from the SP-derived prostatic acid phosphatase (PAP) have been reported to form amyloid fibrils called “SEVI” and enhance HIV-1 infection in vitro. In order to understand the biological consequence of this proviral effect, we extended these studies in the presence of human SP. PAP-derived peptides were agitated to form SEVI and incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Furthermore, physiological concentrations of zinc and copper have been shown to inhibit fibrilization of SEVI in vitro (Sheftic et al, 2012). While not directly applicable to our experiments, one study found the enhancing activity of SEVI to be neutralized in the presence of human seminal fluid through the action of enzymes that degrade SEVI into non-enhancing fragments (Martellini et al, 2011). Another factor that might affect SEVI-mediated enhancement of HIV transmission is whether transmission occurs predominantly through free virus or cell-associated virus, a subject not clearly understood at this time.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, physiological concentrations of zinc and copper have been shown to inhibit fibrilization of SEVI in vitro (Sheftic et al, 2012). While not directly applicable to our experiments, one study found the enhancing activity of SEVI to be neutralized in the presence of human seminal fluid through the action of enzymes that degrade SEVI into non-enhancing fragments (Martellini et al, 2011). Another factor that might affect SEVI-mediated enhancement of HIV transmission is whether transmission occurs predominantly through free virus or cell-associated virus, a subject not clearly understood at this time.…”
Section: Discussionmentioning
confidence: 82%
“…This is a complex microenvironment composed of sperm and seminal lymphocytes (both of which can bind and carry HIV 22–24 ), seminal fluid components, 25,26 and non-HIV sexually transmitted disease pathogens (in the semen donor or the female genital–mucosal tissues 1,2730 ). All of these affect HIV passage across the epithelium and then influence its infectivity and replication in its target cells beneath the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…SE have a role in immunesuppression (17) and affects the complement system (18). It was reported that exposure of the female reproductive tract to semen results in immune-modulatory events which influence the outcome of HIV-1 replication within the genital mucosa (19,20). HIV-1 and human papilloma virus (HPV) is transmitted primarily through sexual contact and semen is the primary vector (21).…”
Section: Sf Contains High Concentration (About 10mentioning
confidence: 99%
“…The correlation between SE, immunity and HIV-1 transmission have been demonstrated (22). SE may either enhance or block replication of sexually transmitted pathogens, such as HIV-1 (19,20). Madison et al showed that semen exosomes purified from healthy human donors alter HIV-1 replication, through alteration in intravirion reverse transcriptase (RT) activity and protein composition, drastically decreasing HIV infectivity (23).…”
Section: Sf Contains High Concentration (About 10mentioning
confidence: 99%